Penerapan Sistem Penyaringan Air Sederhana Untuk Masyarakat Desa Borisallo Kecamatan Parangloe Kabupaten Gowa Provinsi Sulawesi Selatan - Nur Fadliah Baso; Usman; Muhammad Zainal Altim (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Abstract− Water is one of the vital components for human life and all living things in general, starting from the needs of drinking water, irrigation, agriculture, forestry, industry, and many other activities. Because it is very easily contaminated, conservation efforts are needed through an effective and efficient management system so that it can be utilized sustainably for future generations. In Borisallo Village, it has springs that have not been utilized to the fullest. Water from the spring is only flowed through creeks or hoses naturally to residents' homes, without passing through proper storage facilities and adequate water purification systems. By local residents, the water is directly used for daily needs including drinking water, regardless of the risk of disease due to environmental pollution carried by the water flow, which if consumed without good treatment, will have a bad impact on public health. So the purpose of this service is to provide understanding, socialization and the creation of a simple water filtration system to meet the needs of clean water for villagers, as well as provide counseling on maintaining and maintaining water resources. The result obtained is that a simple water purification system built can function properly. The response and participation of residents ranging from socialization, training, trials, and installation of tools is quite good, even residents have been able to create the system independently. Residents' understanding of environmental sustainability and water resources is increasing.